2024
DOI: 10.1021/acs.est.3c09756
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to MEHP during Pregnancy and Lactation Impairs Offspring Growth and Development by Disrupting Thyroid Hormone Homeostasis

Jia Yin,
Shuang Liu,
Yongting Li
et al.

Abstract: phthalate (MEHP), as a highly toxic and biologically active phthalate metabolite, poses considerable risks to the environment and humans. Despite the existence of in vitro studies, there is a lack of in vivo experiments assessing its toxicity, particularly thyroid toxicity. Herein, we investigated the thyroid-disrupting effects of MEHP and the effects on growth and development of maternal exposure to MEHP during pregnancy and lactation on the offspring modeled by SD rats. We found that thyroid hormone (TH) hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Similar studies have shown a direct association between levels of monomeric phthalates including MMP, MBP, MEHP, MEOHP, and MEHHP and lower birth weights (124 and 107 g, respectively), which found that MBP mediated birth weight through gestational age, with each 10-fold increase in exposure resulting in a reduction of birth weight of 85 g . Related studies in animals and cells suggest that exposure to DEHP may lead to changes in serum thyroid hormone levels. , …”
Section: Discussionmentioning
confidence: 62%
“…Similar studies have shown a direct association between levels of monomeric phthalates including MMP, MBP, MEHP, MEOHP, and MEHHP and lower birth weights (124 and 107 g, respectively), which found that MBP mediated birth weight through gestational age, with each 10-fold increase in exposure resulting in a reduction of birth weight of 85 g . Related studies in animals and cells suggest that exposure to DEHP may lead to changes in serum thyroid hormone levels. , …”
Section: Discussionmentioning
confidence: 62%